HUBUNGAN KUALITAS PELAYANAN SDM RUMAH MAKAN GUDEG MBOK MANDEG JOGJAKARTA TERHADAP KEPUASAN PELANGGAN - Retno Djohar Juliani; Heru Sri Wulan; Jazilatul Rohmah (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine the relationship between HR service quality at Gudeg Mbok Mandeg Jogjakarta Restaurant and customer satisfaction. Is quantitative descriptive research. The population in this study were customers at the Mbok Mandeg gudeg restaurant, an average of 600 people in 1 (one) month. The research population is 71 respondents calculated using the Isac and Michael formula. The sampling technique uses incidental random sampling. Data collection techniques using a questionnaire. The measurement technique uses a tiered Likert scale 5. For the quality of HR services, the scales are Very Good, Good, Fairly Good, Not Good, and Very Bad, while customer satisfaction uses the scales Very Satisfied, Satisfied, Fairly Satisfied, Dissatisfied, and Very Dissatisfied. The data obtained is presented in the form of a frequency distribution table and analyzed using cross-tabulations to determine the relationship between HR Service Quality at Gudeg Mbok Mandeg Jogjakarta Restaurant and customer satisfaction. Based on the results of the study, it was found that 2 respondents (3%) stated that the quality of service was very good and customers were very satisfied, as many as 6 respondents (8%) stated that the quality of HR services was good and customers were very satisfied. As many as 6 respondents (8%) stated that the quality of HR services was good and customers were satisfied, 36 respondents (51%) stated that the quality of HR services was good and customers were satisfied. So, it can be concluded that the better the quality of HR services at the Gudeg Mbok Mandeg Jogjakarta Restaurant, the more satisfied the customer will be. As for some suggestions that can be submitted to the Gudeg Mbok Mandeg Restaurant, they can provide a variety of other menus so that customers don't feel bored, restaurant HR can provide explanations to customers about the various food menus available and their prices as material for consideration for customers, home HR Makan Gudeg Mbok Mandeg Jogjakarta should maintain hospitality when there are many visitors at the same time. In addition, the author also provides suggestions so that in the restaurant you can hear the strains of music that are characteristic of "Javanese nuances (gamelan)" in order to add a more pleasant atmosphere for customers.